Furthering our Understanding of the Aetiopathogenesis of Claw Horn Lesions - Wilson, James Patrick (2021)
Claw horn lesions (CHL – sole haemorrhage, sole ulceration, and white line disease) are a prevalent and recurrent cause of lameness in dairy systems globally. These are conditions that compromise the health and welfare of dairy cattle and can challenge the economic viability of a dairy enterprise. Despite our understanding of the importance of these lesions, our knowledge surrounding their pathogenesis remains poor. It has previously been identified that lameness begets lameness and that CHLs are correlated with pathological change to the anatomy of the bovine distal limb. In Chapter 3 it was identified that dairy cattle with a lifetime history of lameness were more likely to have a lower volume of digital cushion in their lateral claws at slaughter. This association and others were explored using a retrospective cohort study. This study involved the hind hooves of 102 Holstein cattle culled from a research herd being scanned using magnetic resonance imaging (MRI). Animal variables including lameness, CHL, body condition score (BCS) were collated for the duration of the animal’s lactating lifetime. The volume and total fat fraction of the digital cushion were calculated using a m-DIXON quant scan sequence. Animals with a history of lameness, CHL occurrence and low BCS were more likely to have less digital cushion in their lateral claws at cull. It was postulated that a weaker genetic and developmental foundation to the digital cushion structure led to certain animals being predisposed to CHLs due to the function of this structure being compromised. These animals then experienced a lifetime of lameness and CHLs which led to the metabolism of digital cushion to facilitate inflammatory pathways. The histology of these digital cushions isolated a vast range in collagen content and adipocyte size in Chapter 4. Animals with a history of lameness in the four weeks before cull tended to have digital cushions with a higher proportion of Type 3 collagen in comparison to Type 1, which is indicative of scarring and inflammatory disease. It was hypothesised that these animals had a higher level of matrix metalloproteinase (MMP – an inflammatory mediator) action local to the hoof which can degrade (and cause the turnover of) collagenous tissues. The treatment and prevention of lameness derived from CHLs may play a vital role in protecting the functional anatomy of the hoof. If this anatomy can be protected, then it is believed that the animal is less likely to experience CHLs in the future. From previous research and that presented in Chapters 3 and 4, the inflammatory aetiology of the CHLs is hypothesised to be a driving force behind the pathological change that occurs. Further to this, there is a growing body of evidence to suggest that inflammation experienced by the dairy cow around the transition period (and the degree to which it exists) can be highly influential on the future health status of the animal. The impacts of transition period inflammation on lameness have never been examined before. Indeed, non-steroidal anti-inflammatory drugs (NSAIDs) have been shown to be important in improving cure rates when used as part of a treatment regimen for CHLs. This has been demonstrated through single outcome measures, however their efficacy in the long-term management of lameness within the dairy herd has never been examined. Chapters 5 and 6 examine the efficacy of NSAID administration in the treatment and prevention of lameness through the implementation of a three-year long randomised controlled trial (RCT). Holstein cattle within the study herd were subjected one of four treatment groups for the entirety of the study period with lameness scoring and treatment administered on a fortnightly basis and a blinded outcome score occurring fortnightly. Chapter 5 asses the impacts of the treatment regimens on the risk of lameness and culling in heifers that calved into the study herd after January 2018. These animals were subjected to treatment regimens from first calving through until the end of the study period or culling. From this study, it was identified that animals that received NSAID at first and subsequent calvings, and at lameness events were at a significantly reduced risk of being scored as lame or culled when compared to those that received no NSAID at calving or lameness. It was hypothesised that systemic inflammation at calving can initiate pathological change to distal limb anatomy which predisposes an animal to CHL onset. Furthermore, the effect size and robust nature of the RCT gives strength to the case for routine administration of NSAID at calving for the purposes of lameness management. The effect size observed presents a substantial opportunity to reduce the prevalence of lameness in the global dairy herd substantially. Chapter 6 examined the effects of NSAID administration as above, but in a cohort of adult dairy cattle that had already calved once prior to study initiation. Contrary to Chapter 5, no effect of NSAID administration at calving or lameness was observed on the risk of an animal being scored as lame or culled from the herd. It could be suggested that these animals have already had some degree of pathological change to distal limb anatomy associated with either transition or lameness which has led to a predisposition to future lameness which cannot be undone. This predisposition may counteract any benefits associated with NSAID administration as a treatment or prevention, meaning that with regards to long term lameness management, there is little if any positive prospect for animals that have been previously lame or calved without NSAID administration. This thesis, however, does not diminish the importance of the pain management associated with NSAID administration. This thesis furthers our understanding of pathological change to distal limb anatomy and optimal treatment and prevention regimens for lameness in dairy cattle. Presented within Chapter 5 and 6 is the longest running RCT conducted to date investigating lameness treatments with longitudinal outcomes. This has provided a robust evidence base for informed, impactful management practices to be implemented, and has provided evidence for further hypothesis to be framed around.